DEVELOPMENT OF INTERACTIVE MEDIA AS FAMILY ASSISTANCE TO PREGNANT WOMEN IN IMPROVING QUALITY OF LIFE - Dina Putri Utami Lubis; Mita Meilani; Risky Puji Wulandari (IAKMI South Tangerang Branch, 2023)
Background: Pregnancy is a physiological or natural condition that can occur physical and emotional changes. One way to improve the quality of life (QOL) is with family assistance. Interactive learning media is a learning method based on information and communication technology. Objective:To analyze the quality of life of pregnant women who are given interactive media as family assistance. Method: Quasi Experimental research design with Non-equivalent pre-test and post-test control group design. The quality of life instrument used in this study uses WHOQOL-Bref which consists of 26 questions with a Likert scale. Samples were taken by purposive sampling as many as 108 pregnant women who were divided into 2 intervention and control groups spread across at works area of Sleman Primary Health Centre. Results: The average increase in QOL for pregnant women in the intervention group was 1.74 and in the control group the average increase in QOL for pregnant women was 0.65. Mann-Whitney statistical test 0.025 (<0.05) which means there is a difference in the increase in QOL of pregnant women in the group of mothers who were given interactive media in the form of learning videos and those who were not given videos. Conclusion: Theres a significant difference in increasing the Quality of Life for pregnant women before and after providing interactive media in the form of learning videos. Health workers are advised to make interactive media as a form of promotive and preventive efforts for maternal and child health services. Keywords: Quality of Life, Interactive Media, Pregnant Women